PARIWISATA DI ERA OTONOMI KHUSUS PAPUA (Sebaran dan Ancaman) - Hugo Warami (Jurnal Ilmiah Hospitality Management, 2012)
The authority and capability in the financial resources to dig them fairly wide open now through the implementation of Law No. 21 of 2001 on Special Autonomy. Therefore, local governments have the opportunity to explore the potential of the regions, in collaboration with public and private sectors in efforts to optimize revenue (PAD), through the tourism services sector. In line with the mandate of the special autonomy, the local community through the tourism sector need to be empowered through the principle of partnership to community groups marginalized, oppressed and those in the lower layers of the social structure in accordance with the spirit and values of the basic law. On the other hand,Â  it is expected the distribution of the tourism sector to be the starting point of the process of change, which changes the state of the oppressed who have been neglected status and dignity for the better and more empowered. In addition, there appeared a general trend to escape or emancipation from the domination of a social group for another social group becomes a serious threat in the development of the tourism sector in Papua.